Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
ugh math question =[ i need to know the steps, someone help.?
okay this is the question...oh and those dashes or slashes w.e they're called are the little bars for the graphs.. anyways i kneed to know the step by step explination...i feel bumb asking this cause i should have learned this a long time ago but i'm having trouble...i'm not sure if i could just add it all or do i have to have a common denominator and stuff.
5z-4/4 + 7z-4/3 =12
7 Answers
- wildeyedredheadLv 51 decade agoFavorite Answer
5z-4/4 + 7z-4/3 =12
12(5z-4/4 + 7z-4/3) =12
60z - 12 + 84z - 16 = 12
144 z - 28 = 12
144z = 12+ 28
144z = 40
z = 7.2
- mrvadeboncoeurLv 71 decade ago
Hm, not sure which equation you have here...
5z-(4/4) + 7z-(4/3) =12
or
(5z-4)/4 + (7z-4)/3 =12
Now, remember that you can add/subtract/multiply/divide by the same amount on both sides of an equals equation, and still keep the equality. You want to solve for the variable, in this case z, by isolating it all on one side of the equation and having its multiplier equal to 1.
5z-(4/4) + 7z-(4/3) = 12
reorder:
5z + 7z - (4/4) - (4/3) = 12
12z - 12/12 - 16/12 = 12
12z - 28/12 = 144/12
12z - 28/12 + 28/12 = 144/12 + 28/12
12z = 172/12
12z/12 = (172/12) * (1/12)
z = 172/144
(5z-4)/4 + (7z-4)/3 =12
12 * {(5z-4)/4 + (7z-4)/3} = 12*12
3*(5z-4) + 4*(7z-4) = 144
15z - 12 + 28z - 16 = 144
15z + 28z -12 -16 = 144
43z - 28 = 144
43z - 28 + 28 = 144 + 28
43z = 172
43z/43 = 172/43
z = 4
(so yes, when you add two fractions together, they need a common denominator.)
- Anonymous1 decade ago
The problem to solve is:
5z-4/4 + 7z-4/3=12
First, let's work on the left hand side of your equation, the 5z-4/4 + 7z-4/3
This means, for instance, to see if it can be simplified at all.
Multiply z and 5
Multiply z and 1
The z just gets copied along.
The answer is z
z
5*z evaluates to 5z
4/4 evaluates to 1
5*z-4/4 evaluates to 5z-1
Multiply z and 7
Multiply z and 1
The z just gets copied along.
The answer is z
z
7*z evaluates to 7z
5z + 7z = 12z
The answer is 12z-1
5*z-4/4+7*z evaluates to 12z-1
4/3 evaluates to 4 over 3.
- 1 decade ago
5z-4/4 +7z-4/3=12
4z+7z
11z-4/3=12
+4/3
cross the 4/3
minus 4/3 out.
and add 4/3 to 12
bring down ur 11z so u get.
11z=12 4/3
divide 12 by 11
u get 1 and 4/3
- How do you think about the answers? You can sign in to vote the answer.
- 1 decade ago
I'm not quite sure of this,but you might meant this:
((5z-4)/4)+((7z-4)/3)=12
If this is it,
3(5z-4)+4(7z-4)=144
15z-12+28z-16=144
43z=172
z=4
If it is not like shown above,you may refer other answers.
- joe cLv 61 decade ago
5z-4/4+7z-4/3=12
5z-1+7z-11/3=12
the problem is incorrect so its no wonder youu can't find the solution